The concept of sin in Kierkegaard: A study from the works “The Concept of Anxiety” and “The Sickness Unto Death” - Hintz, Bruno Bernardi; Schwambach, Claus (Vox Scripturae - Revista Teológica Internacional, 2016)
This essay is a study of the meaning of sin inside the Kierkegaard’s work, starting from two of his publications. Initially, to locate us in the subject, we will go through general aspects of the philosophy and life of Kierkegaard. Following it will treat the concept of sin in the work “The Concept of Anxiety”, and after in the work “The Sickness Unto Death” seeking to understand the sin inside of the general frame of each writing, in its connection with the facts of the human subjectivity discussed by the philosopher. Ultimately, it will make a synthesis of the Kierkegaard’s thinking about the sin and it will think the relation between anguish and desperate inside the relation of them with the sin.
Keywords: Sin; Anguish; Desperate; Philosophy; Theology